Keynes and Hayek betrayed: on the curious stance of Europe's Keynesian and libertarian political economists in the context of the eurozone crisis. (1st January 2012) - Varoufakis, Yanis
Following the Crash of 1929, an epic debate began between liberals, led by Friedrich von Hayek, who believed in capitalism's automatic stabilisers and John Maynard Keynes who did not. Today, in Europe, this debate has taken an interesting twist. On the one hand, most libertarians have succumbed to the conventional wisdom of the eurozone's massive bailouts; while on the other, the majority of Keynesians have adopted analyses that deny much that was central to Keynes' thinking about macroeconomies caught in the clutches of debt-recessionary cycles. This paper sums up these internal inconsistencies of European libertarians and Keynesians and hints at explanations regarding the reasons behind them.